EKSPLORASI ETNOMATEMATIKA PADA RUMAH ADAT SUKU BADUY di PROVINSI BANTEN - yulyani, yayan (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2023)
The traditional house of the Baduy Tribe is one of the cultural heritages located in Lebak Regency, Banten. The purpose of this study is to find out the material in mathematics learning that is relevant to the mathematical aspects of the Baduy traditional house. This research method is descriptive qualitative with an ethnographic approach and the data sources are obtained from observations, documentation and interviews related to the traditional house of the Baduy tribe in the province of Banten. In this study using triangulation techniques to test the credibility of the data. The results showed that: 1) The symbolic meaning contained in the traditional house of the Baduy tribe as a repellent for reinforcements or the safety of the Baduy community and believing that the symbol would bring abundant sustenance, 2) The mathematical concepts in the traditional house of the Baduy tribe include: a. Flat shapes are squares, rectangles, rhombuses, and triangles. b. Build spaces, namely: cubes, blocks, and triangular prisms.